Shade me - Brown, Jennifer, 1972- (New York, NY : Katherine Tegen Books, an imprint of HarperCollins Publishers, 2016)
"A teenage girl with special cognitive abilities becomes embroiled in a mystery surrounding the brutal attack of a high-profile classmate and a sexy yet dangerous relationship with a stranger"--
Keywords: Detective and mystery stories; Synesthesia -- Fiction